DESCRIPTIVE ANALYSIS OF CASES OF DOMESTIC VIOLENCE, CHILD SEXUAL ABUSE AND EXPLOITATION, AND HUMAN TRAFFICKING, BASED ON THE HOPE & JUSTICE FOUNDATION SYSTEM - Alves-Lazaro, Anna (Revista Gênero e Interdisciplinaridade, 2025)
Introduction: Domestic violence is characterized as a form of physical, psychological, sexual, economic, or social abuse committed within the domestic environment, usually among family members or people living in the same space. In this context, descriptive mappings of domestic violence can help identify patterns of occurrence, vulnerable groups, and specific contexts where violence is more prevalent. Objective: To describe cases of domestic violence, child sexual abuse and exploitation, and human trafficking, based on data from the Hope & Justice Foundation system. Methodology: The research adopts a quantitative approach and is a descriptive study. The study population consisted of 473 individuals assisted by the Hope & Justice Foundation from 2022 to 2024. Results: The research found that between 2022 and 2024, the Hope & Justice Foundation primarily assisted women (93.24%). Domestic violence was the most prevalent crime, accounting for 81.82% of the cases, followed by child sexual abuse and exploitation (15.64%) and human trafficking (6.55%). Most victims were Brazilian, with a gradual increase in victims of other nationalities over the years. The nationality of the aggressors was predominantly Brazilian, with annual variations and a notable increase in the number of identified aggressors. Conclusion: We can conclude that there is a growing diversity in the nationalities of both victims and aggressors over the years. These results highlight the importance of targeted interventions to mitigate different types of violence and support victims, as well as the need for effective and inclusive public policies to address the complexity of these issues.